Mutant GNLY is linked to Stevens–Johnson syndrome and toxic epidermal necrolysis (2019)
Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are rare severe cutaneous adverse reactions to drugs. Granulysin (GNLY) plays a key role in keratinocyte apoptosis during SJS/TEN pathophysiology. To determine if GNLY-encoding mutations might be related to the protein’s functional disturbances, contributing to SJS/TEN pathogenesis, we performed direct sequencing of GNLY’s coding region in a group of 19 Colombian SJS/TEN patients. A GNLY genetic screening was implemented in a group of 249 healthy individuals. We identified the c.11G > A heterozygous sequence variant in a TEN case, which creates a premature termination codon (PTC) (p.Trp4Ter). We show that a mutant protein is synthesised, possibly due to a PTC-readthrough mechanism. Functional assays demonstrated that the mutant protein was abnormally located in the nuclear compartment, potentially leading to a toxic effect. Our results argue in favour of GNLY non-synonymous sequence variants contributing to SJS/TEN pathophysiology, thereby constituting a promising, clinically useful molecular biomarker. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.